THE MEDIATING EFFECT OF CAREER ADAPTABILITY BETWEEN WORK SOCIAL SUPPORT, STRESS, SATISFACTION, AND TURNOVER INTENTION ON PRIVATE SECTOR EMPLOYEES - Efrial, Annisa Syafira; Satrya, Aryana (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
This study aims to determine the effect of work social support on turnover intention mediated by career adaptability, the effect of work stress on turnover intention mediated by career adaptability, the effect of work social support on work satisfaction mediated by career adaptability, the effect of work stress on work satisfaction mediated by career adaptability, and the effect of career adaptability on turnover intention mediated by work satisfaction. This research uses quantitative research methods. Data collection is done through primary data and secondary data. In this study, primary data was collected through an online questionnaire using Google Form, which was filled in by respondents independently. The questions in the questionnaire are closed-ended and use different measurement scales for each variable. The data that has been collected is then analyzed using the SEM (Structural Equation Modeling) method. The results showed that work social support, work stress has a positive and significant effect on turnover intention mediated by career adaptability. Then, work social support, work stress has a positive and significant effect on work satisfaction mediated by career adaptability. While career adaptability has no influence on turnover intention mediated by work satisfaction.